Análisis financiero con valorización de la empresa sociedad minera Cerro Verde S.A.A - Valdivia Sánchez, José Adrián (2024)
This study aims to coduct a comprehensive financial analysis and determine the real value of Sociedad Minera Cerro Verde (SMCV). It operates one of the largest open-pit copper mines in the world, located in the Arequipa región, Perú. Globally, copper remains a high-demand resource, driven by the electrical, construction, and technological industries. The analysis starts with a global Peruvian economic study, where the mining sector in one of the fundamental pillars of the country ́s economy. From a financial perspective, SMCV ́s analysis shows stable liquitidy, solvency, and profitability ratios. The dividend policy has aslo been stable, maintaing a consistent dsitribution to shareholders. The study aslo includes an evaluations of SMCV ́s financial statements and future revenue projections. Using the discounted cash flow (DFC) method, a significant value is projected, based on the company ́s ability to generate sustainable future income. Regarding risks, the company identifies operational risks such as exposure to price fluctuations, regulatory and social risks, and dependency on international markets. These are mitigated through appropiate management and diversification strategies. In conclusion, SMCV stans out a key player in the Peruvian mining industry, with operational and financial capabilities. It positions itself as an attractive investment for those looking to participate in the growth of tge mining sector. Its adaptability and commintment to sustainability make it a promising company, offeing excelente long-term value creation prospects.